Participatory literacy practices for P-12 classrooms in the digital age - Mitchell, Jessica S.; Vaughn, Erin N. (IGI Global, 2020)
""This book explores the role of participatory literacy in P-12 student learning through digital instruction. It also addresses current issues in teacher education which can be applied to a broad educational context"--Provided by publisher"--